Comprehensive Evaluation of Dietary Nutrition Based on Normalization and Linear Weighted Model - Huang, Yiqi (Transactions on Environment, Energy and Earth Sciences, 2024)
Dietary recipes play a pivotal role in maintaining nutritional health. A balanced and scientific diet can enhance nutrient absorption and preserve physical well-being. Nevertheless, many dietary nutritional assessment methods suffer from the limitation of being partial or one-sided. To address this issue and better facilitate the search and design of dietary plans, we have employed a normalized and refined linear weighted method to construct a novel comprehensive evaluation model. This approach eliminates the influence of different dimensions, allowing various types of indicators to be compared and analyzed simultaneously. Therefore, it enables a holistic evaluation of multiple nutritional indicators, yielding a comprehensive result. Furthermore, we illustrate the application of this model with a daily dietary plan for a male college student as an example. Based on the fundamental principles of balanced diets and food information, a comprehensive nutritional evaluation of the diet is conducted. This model not only facilitates the design of scientific dietary plans but also aids individuals in cultivating healthy eating habits, thereby safeguarding their overall health.